Evaluasi Penerapan Sistem Otomasi Senayan Library Management System (SLiMS) Menggunakan Model Human Organization Technology (HOT) Fit di Perpustakaan UIN Imam Bonjol Padang - Husra, Qurrhatu Aini; Nelisa, Malta (ARZUSIN, 2024)
A communication information technology system, SLiMS is an application for library management. However, in the implementation of SLiMS, there are still issues such as missing collections on shelves, server downtimes, some patrons not knowing how to use SLiMS, and limited promotion of SLiMS usage. The objective of this research is to evaluate the implementation of SLiMS using the HOT Fit model. This study employs a quantitative research method with a descriptive approach. The research sample consists of 100 library patrons, and data were collected through questionnaire distribution to respondents who met the research criteria. Based on the data obtained, the research findings indicate the following: The implementation of the SLiMS automation system at UIN Imam Bonjol Padang Library in the human (people) indicator is categorized as very high, falling within the interval scale of 3.26 – 4. The implementation of the SLiMS automation system at UIN Imam Bonjol Padang Library in the organization indicator is categorized as high, falling within the interval scale of 2.6 – 3.25. The implementation of the SLiMS automation system at UIN Imam Bonjol Padang Library in the technology indicator is categorized as high, falling within the interval scale of 2.6 – 3.25. Therefore, it can be concluded that the implementation of the SLiMS automation system at UIN Imam Bonjol Padang Library is considered good.